Widespread intracranial calcifications in the follow-up of a patient with cartilage-hair hypoplasia – Anauxetic dysplasia spectrum disorder: A coincidental finding?. (May 2015) - Garcia-Tarodo, S.; Bottani, A.; Merlini, L.; Kaelin, A.; Schwitzgebel, V.M.; Parvex, P.; Dayer, R.; Lascombes, P.; Korff, C.M.
Abstract Background/purpose Intracranial calcifications have been identified in many neurological disorders. To our knowledge, however, such findings have not been described in cartilage-hair hypoplasia – anauxetic dysplasia spectrum disorders (CHH-AD), a group of conditions characterized by a wide spectrum of clinical manifestations. Methods/results We report a 22-year old female patient, diagnosed with this disorder during her first year of life, and in whom bilateral intracranial calcifications (frontal lobes, basal ganglia, cerebellar dentate nuclei) were discovered by brain MRI at the age of 17 years. Conclusion The etiology of this finding remains unclear. Some causes of such deposits can be of a reversible nature, thus prompting early recognition although their consequences on clinical outcome remain mostly unknown.